Tanbûr long-necked lutes along the Silk Road and beyond - Zeeuw, Hans de, (Archaeopress archaeology., 2019)
This text is divided into two main parts: 'The Tanbûr Tradition' which discusses the origin, history, construction and playing techniques of tanbûrs; and 'The Tanbûr Family' which focuses on long-necked as a family of musical instruments. After a short introduction, the construction, playing technique, and musical traditions are briefly discussed.